Ultrahigh Adhesion Force Between Silica-Binding Peptide SB7 and Glass Substrate Studied by Single-Molecule Force Spectroscopy and Molecular Dynamic Simulation - Zhang, Xiaoxu; Chen, Jialin; Li, Enci; Hu, Chunguang; Luo, Shi-Zhong; He, Chengzhi (Frontiers in Chemistry, 2020)
Many proteins and peptides have been identified to effectively and specifically bind on certain surfaces such as silica, polystyrene and titanium dioxide. It is of great interest, in many areas such as enzyme immobilization, surface functionalization and nanotechnology, to understand how these proteins/peptides bind to solid surfaces. Here we use single-molecule force spectroscopy (SMFS) based on atomic force microscopy to directly measure the adhesion force between a silica-binding peptide SB7 and glass surface at single molecule level. SMFS results show that the adhesion force of a single SB7 detaching from the glass surface distributes in two populations at 220 pN and 610 pN, which is higher than the unfolding forces of most mechanically stable proteins and the unbinding forces of most stable protein-protein interactions. Molecular dynamics simulation reveals that the electrostatic interactions between positively charged arginine residues and the silica surface dominates the binding of SB7 on silica. Our study provides experimental evidence and molecular mechanism at the single-molecule level for the SB7-based immobilization of proteins on silica-based surface, which is able to withstand high mechanical forces, making it an ideal fusion tag for silica surface immobilization or peptide-base adhesive materials.